Respostas
respondido por:
2
Dados: A = 2x + 3y; B = (2x - 3y).
a) 2A =
2 * (2x + 3y) =
4x + 6y
b) 2B =
2 * (2x - 3y) =
4x - 6y
c) A² =
(2x + 3y)² =
2x² + 6xy + 3y²
d) B² =
(2x - 3y)² =
2x² - 6xy + 3y²
e) AB =
(2x + 3y) * (2x - 3y) =
4x² - 6xy + 6xy - 9y² =
4x² - 9y²
Espero ter ajudado!
a) 2A =
2 * (2x + 3y) =
4x + 6y
b) 2B =
2 * (2x - 3y) =
4x - 6y
c) A² =
(2x + 3y)² =
2x² + 6xy + 3y²
d) B² =
(2x - 3y)² =
2x² - 6xy + 3y²
e) AB =
(2x + 3y) * (2x - 3y) =
4x² - 6xy + 6xy - 9y² =
4x² - 9y²
Espero ter ajudado!
Lets3210:
OI ME AJUDA COM MAIS UMA ?
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás